ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI PADI SAWAH DI DESA MARANATHA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Lagebada, Dennis Reynhard; Effendy, Effendy; Sulaeman, Sulaeman (AGROTEKBIS, 2017)
This study aimed to determine the income and the feasibility of wetland rice farming in Maranatha village, Sigi Biromaru sub district of Sigi district.The location was determined purposively whererespondents were selected using a simple random sampling technique and the number of the samples using Slovin formula. The Samples were 38 households taken from 280 farmer households with the error of approximately 15%. The analysis used wasthe income analysis (Ï) and feasibility analysis (R/C). The results showed that the mean value of the respondents income in one planting period was about IDR 8,150,109/1.04 ha or IDR 7,836,643.33/ha. The result of R/C analysis was 2.00 indicating that every IDR 1spent will generate income of about IDR 2.00. Therefore, it is feasible for the rice farming to be developed in Maranatha.Â Key Words:Â  Farming, feasibility, income, paddy.